Predicting 30-day mortality in patients with sepsis: an exploratory analysis of process of care and patient characteristics - Sanderson, Miriam; Chikhani, Marc; Blyth, Esme; Wood, Sally; Moppett, Iain K.; McKeever, Tricia; Simmonds, Mark J.R. (SAGE Publications, 2018)
Background